2018
DOI: 10.1155/2018/4036709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pulmonary and Systemic NO‐ and PGI2‐Dependent Endothelial Function in Diabetic Mice

Abstract: Diabetes increases the risk of pulmonary hypertension and is associated with alterations in pulmonary vascular function. Still, it is not clear whether alterations in the phenotype of pulmonary endothelium induced by diabetes are distinct, as compared to peripheral endothelium. In the present work, we characterized differences between diabetic complications in the lung and aorta in db/db mice with advanced diabetes. Male, 20-week-old db/db mice displayed increased HbA1c and glucose concentration compatible wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…On the other hand, S961 induced robust hyperglycemia and severe increase in HbA1c to the levels similar as in advanced-aged diabetic db/db mice [40,41], robust increase in GTT (much more pronounced than in the HFD model) and alterations in various RBCrelated indices including increased GSH/GSSH ratio in RBCs. Interestingly, the connection between diabetic erythropathy and endothelial dysfunction was suggested recently [42], and could be relevant in the context of the profound endothelial dysfunction in the S961treated animals.…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, S961 induced robust hyperglycemia and severe increase in HbA1c to the levels similar as in advanced-aged diabetic db/db mice [40,41], robust increase in GTT (much more pronounced than in the HFD model) and alterations in various RBCrelated indices including increased GSH/GSSH ratio in RBCs. Interestingly, the connection between diabetic erythropathy and endothelial dysfunction was suggested recently [42], and could be relevant in the context of the profound endothelial dysfunction in the S961treated animals.…”
Section: Discussionmentioning
confidence: 65%
“…Importantly, the occurrence of EndMT in pulmonary circulation coincided with endothelial dysfunction in the aorta ( Figures 1 , 3 ), which are both associated with preserved and impaired NO-dependent function, respectively, underscoring the phenotypic heterogeneity of age-dependent changes in the aorta and pulmonary circulation. Interestingly, we recently observed phenotypic heterogeneity in systemic and pulmonary endothelium in response to diabetes ( Fedorowicz et al, 2018 ). Nevertheless, the co-occurrence of early-stage EndMT in the lungs and impaired endothelium-dependent vasodilation in TA and AA suggest that assessing age-dependent peripheral endothelial dysfunction may be of potential diagnostic and predictive value when evaluating the adverse response of the pulmonary endothelium to an insult resulting in EndMT.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually regarded as the main regulator of blood vessels. When endothelial cells proliferate rapidly, the secretory expression of PGI2 will increase significantly [ 32 ]. In previous studies, researchers had found that in patients who have type 2 diabetes or atherosclerosis, the excessive proliferation of endothelial cells was associated with excessive secretion of PGI2.…”
Section: Discussionmentioning
confidence: 99%